Transfusion related acute lung injury: a case report - Alcazar Castro, Javier; Zárate Aspiros, Alejandro; Andrade Cuellar, Elias N.; Álvarez Pérez, Brenda M.; Valderrama Treviño, Alan Isaac; Granados Romero, Juan J.; Banegas Ruiz, Rodrigo; Barrera Mera, Baltazar (International Journal of Research in Medical Sciences, 2018)
Transfusion Related Acute Lung Injury (TRALI) is one of the most serious complications of blood transfusion. All blood components have been implicated and most often those that contain plasma. The diagnosis is based fundamentally on the integration of clinical, radiological and gasometry elements, once the rest of the possible causes of acute lung injury have been ruled out. The differential diagnosis of a patient who develops a sudden pattern of respiratory failure after a transfusion of blood products must include hemodynamic overload, anaphylactic reaction, bacterial contamination of transfused blood products, haemolytic transfusion reaction and TRALI. Author presented the clinical case of a 33-year-old female patient with grade III hypovolemic shock due to a ruptured ectopic pregnancy, reanimated with crystalloid solutions, globular packages and fresh frozen plasma. The patient developed TRALI for what was managed with ventilatory and hemodynamic support in ICU.